Stage-specific concurrent chemoradiotherapy with or without induction chemotherapy for locoregionally advanced nasopharyngeal carcinoma: a retrospective, population-based study - Xia WX; Liang H; Lv X; Wang L; Ye YF; Ke LR; Xu LH; Guo X; Xiang YQ (Cancer Management and Research, 2019)
Wei-Xiong Xia,1,2,* Hu Liang,1,2,* Xing Lv,1,2 Lin Wang,1,2 Yan-Fang Ye,3 Liang-Ru Ke,1,2 Lin-Hao Xu,4 Xiang Guo,1,2 Yan-Qun Xiang1,2 1State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangdong Key Laboratory of Nasopharyngeal Carcinoma Diagnosis and Therapy, Sun Yat-sen University Cancer Center, Guangzhou 510060, People’s Republic of China; 2Department of Nasopharyngeal Carcinoma, Sun Yat-sen University Cancer Center, Guangzhou, People’s Republic of China; 3Sun Yat-Sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 4IBM Research China, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiang Guo; Yan-Qun XiangDepartment of Nasopharyngeal Carcinoma, Sun Yat-Sen University Cancer Center, 651 Dongfeng Road East, Guangzhou 510060, People’s Republic of ChinaTel +86 208 734 3392; +86 208 734 3379Email guoxiang@sysucc.org.cn; xiangyq@sysucc.org.cnPurpose: This large population-based analysis aims to investigate whether the additional induction chemotherapy to concurrent chemoradiotherapy improved overall survival (OS) and disease-free survival (DFS) for locoregionally advanced nasopharyngeal carcinoma (LRANPC).Patients and Methods: The study group comprised 3,980 patients who were treated either with IC+CCRT (1,888 patients) or CCRT alone (2,092 patients) between January 1998 and June 2013. Survival outcomes were compared using Cox proportional hazards regression models with adjustments for confounding provided by propensity score methods. Primary outcome variables included OS and DFS.Results: Kaplan–Meier analysis showed that CCRT and IC+CCRT were of similar benefit to OS (P=0.099), whereas there was a marginal benefit of CCRT to DFS (P=0.063) in the overall cohort, which showed no differences between the two treatment regimens using multivariate Cox analysis and propensity score. Interestingly, for patients with 2D radiationtherapy (2DRT), CCRT had OS and DFS benefits for stage III, with 5-year and 10-year OS for CCRT vs IC+CCRT being 88% and 75% vs 81% and 67%, respectively (P=0.002); 5-year and 10-year DFS for CCRT vs IC+CCRT being 84% and 74% vs 76% and 66%, respectively (P=0.002). In contrast, IC + CCRT had OS and DFS benefits for stage IVa-b, with 5-year and 10-year OS for CCRT vs IC+CCRT being 71% and 55% vs 76% and 60%, respectively (P=0.037, HR=0.786); 5-year and 10-year DFS for CCRT vs IC+CCRT were 64% and 50% vs 69% and 58%, respectively (P=0.038, HR=0.801). No difference was found in intensity-modulated radiotherapy (IMRT) subgroup.Conclusion: Our study indicates that CCRT and IC+CCRT may have similar OS and DFS benefits for overall LRANPC. Stage-specific chemoradiotherapy may be administered based on the greatest benefit of IC+CCRT for stage IVa-b patients and CCRT alone for stage III patients received 2DRT. The optimal chemotherapy pattern in combination with IMRT needs further investigation.Trial registration: ClinicalTrials.gov ID: NCT02604472Keywords: nasopharyngeal carcinoma, concurrent chemotherapy, radiation therapy, induction chemotherapy, prognosis, stage specific